Plant protein-based delivery systems for bioactive ingredients in foods. Issue 9 (2nd September 2015) - Wan, Zhi-Li; Guo, Jian; Yang, Xiao-Quan
<x xml:space="preserve">Abstract</x> The application of food-grade delivery systems for the encapsulation, protection and controlled release of bioactive food ingredients have recently gained increasing interest in the research fields of functional foods and pharmaceutics. The preparation and application of bifunctional particles provide a novel perspective for the design of plant protein-based delivery system.